Identifikasi Sifat Fisik, Kimia, dan Sensoris Klon-klon Harapan Ubijalar Kaya Antosianin - Ginting, Erliana; Yulifianti, Rahmi; Jusuf, M.; Mejaya, Made J. (Jurnal Penelitian Pertanian Tanaman Pangan, 2015)
Breeding for sweet potato varieties rich in anthocyanins is essential to promote the use of sweet potato as functional food as well as to support food diversification program. This study was performed to identify physical, chemical, and sensorial characteristics of 10 promising clones of purple-fleshed sweet potato and two varieties (Ayamurasaki and Antin 1) as checks, at the Food Chemistry and Processing Laboratory of ILETRI, Malang from November until December 2012. The trial was arranged in a completely randomized design with three replicates. Observations included physical and chemical characteristics of the fresh roots and sensory attributes of the steamed roots using hedonic test of 20 panelists. The flesh colour varied from white/yellow purplish, purple up to dark purple. The lightness colour (L*) of root flesh was negatively correlated with total anthocyanins (R2 = 0.81), which varied from 1.86 mg (MSU 06044-05) up to 123.92 mg equivalent to cyanidin 3-glycoside/100 g fw (MSU 06046-48). Three clones, namely MSU 06046-48, MSU 06028-71, and MIS 0601-179 had higher total anthocyanins than that of Ayamurasaki (70.41mg/100 g fw) as a check. Moisture, ash, crude fiber, reducing sugar, amylose, and starch contents also varied among clones, ranged from 67.7 to 75.8%; 2.8 to 3.9% dw; 2.5 to 4.8%; 0.9 to 4.4% dw; 20.0 to 27.4% dw and 50.3 to 66.6% dw, respectively. MIS 0601-179 clone had the highest dry matter and starch contents (40.05% dw and 66.64% dw) which were suitable for flour ingredient. The steamed roots of MSU 06044-05 (yellow purplish) gave the highest scores of panelist preferences on colour, texture and taste attributes, followed by MIS 0601-179, Ayamurasaki, and MSU 06028-71 (purple). The bitter taste of MSU 06046-48 steamed roots associated with the highest anthocyanins content was slightly disliked, suggesting that this clone needs an alternative preparation method other than steaming.